Validation of the General Medication Adherence Scale in Saudi Patients With Chronic Diseases - Naqvi, Atta Abbas; AlShayban, Dhafer Mahdi; Ghori, Syed Azizullah; Mahmoud, Mansour Adam; Haseeb, Abdul; Faidah, Hani Saleh; Hassali, Mohamed Azmi (Frontiers in Pharmacology, 2019)
Objective: The aim was to validate the General Medication Adherence Scale (GMAS) (English version) in Saudi patients with chronic disease. Methods: A month-long study was conducted in the out-patient department of tertiary care hospitals in three cities of Saudi Arabia that collected data from a randomized sample of Saudi patients with chronic disease. The study aimed to achieve an item-to-subject ratio greater than 1:10. Factor analyses were conducted and fit indices calculated. Convergent, discriminant, known group, and concurrent validities were analysed. Internal consistency was determined using test–retest reliability using Cronbach’s alpha (α), McDonald’s coefficient omega (ωt), and Pearson’s correlation coefficient (ρ). Sensitivity analysis was conducted. Data were analysed through Statistical Package for Social Sciences (SPSS) version 23. The study was ethically approved (i.e., IRB-129-26/6/1439). Results: The survey gathered responses from 171 patients with a response rate of 85.5%. An item-to-subject ratio of 1:15 was achieved. Factor analysis revealed a three-factor structure with acceptable fit indices (i.e., normed fit index (NFI) = 0.93, Tucker–Lewis index (TLI) = 0.99, and comparative fit index (CFI) = 0.99), i.e., greater than 0.9. The value of root mean square error of approximation (RMSEA) was 0.01, i.e., less than 0.08. The tool established construct validity, i.e., convergent and discriminant validities. Known group and concurrent validities were also established. An α value of 0.74 and ωt value of 0.92 were reported. Test–retest reliability ρ = 0.82, p < 0.001. The tool had high sensitivity (>75%) and specificity (>80%). Conclusion: The GMAS-English was successfully validated in Saudi patients with chronic disease.